Making mirrors: premotor cortex stimulation enhances mirror and counter-mirror motor facilitation. - Catmur, C; Mars, R; Rushworth, M; Heyes, C (2011)
Mirror neurons fire during both the performance of an action and the observation of the same action being performed by another. These neurons have been recorded in ventral premotor and inferior parietal cortex in the macaque, but human brain imaging studies suggest that areas responding to the observation and performance of actions are more widespread. We used paired-pulse TMS to test whether dorsal as well as ventral premotor cortex is involved in producing mirror motor facilitation effects. Stimulation of premotor cortex enhanced mirror motor facilitation and also enhanced the effects of counter-mirror training. No differences were found between the two premotor areas. These results support an associative account of mirror neuron properties, whereby multiple regions that process both sensory and motor information have the potential to contribute to mirror effects.